Possibilities for utilization of dietary fiber-rich supplement from pepper (Capsicum annum L.) processing waste in bakery products - Jasna Mastilović; Žarko Kevrešan; Milan Vukić; Marko Ivanović; Jelena Radovanović; Dženita Džinić (Journal of Engineering & Processing Management, 2018)
By the application of processes of stabilization through drying,separation of seed and grinding of remaining placenta dietaryfiber-rich powdered product was obtained from pepper (Capsicumannum L.) processing waste. Effects of dosing of pepper placentabasedsupplement (1, 2 and 3%) on farinograph, extensographand amylograph parameters, as well as test baking, wereconducted in this study.Addition of pepper placenta-based supplement resulted in anincrease of farinograph water absorption in obtaining of darkerand more intensively colored bread crust and in smaller and moreevenly distributed pores of breadcrumb. It also inhibited thefirming of breadcrumb during bread shelf life. The main negativeeffects of the application of placenta-based supplement were theincrease of dough resistance and the decrease of breadcrumbcohesiveness.
Keywords: Bakery; fiber; pepper; products; waste